Modern views on the molecular and vascular mechanisms of preeclampsia - Shumilina , Tetiana; Slyvka, Yaroslava (The Ukrainian Scientific Medical Youth Journal, 2021)
the article summarizes the arguments and counterarguments in the scientific discussion on the mechanisms of preeclampsia. The main purpose of this study is to summarize information about the molecular and vascular mechanisms of preeclampsia. Thanks to a detailed study of literature sources, their systematization and approaches to solving the problem, it was found that genetic and environmental factors cause placental maladaptation, which leads to defective placentation, apoptosis of invasive cytotrophoblasts, inadequate expansive remodeling of spiral arteries. The relevance of the study of this pathology is that it largely determines the perinatal and maternal morbidity. However, today there is no clear idea about the features of the molecular and vascular mechanisms of preeclampsia, which leads to inconsistencies in the treatment of such pregnant women, which averts timely, adequate treatment and prevention. The bibliosemantic method and the content analysis of the literature concerning questions of new researches on features of mechanisms of development of preeclampsia were used. The article presents the results of studies that have shown that placental ischemia promotes the release of bioactive factors into the maternal circulation, causing an imbalance between antiangiogenic soluble tyrosine kinase-1, soluble endoglin and proangiogenic vascular endothelial growth factor stimulates the release of proinflammatory cytokines, hypoxia-inducing factor, reactive oxygen species and agonistic autoantibodies to type 1 angiotensin receptors. These circulating factors target the vascular endothelium, causing generalized endotheliosis in the systemic, renal, cerebral, and hepatic vessels, and lead to a decrease in vascular dilators such as nitric oxide, prostacyclin, hyperpolarization factor, and increased vasoconstrictors such as endothelin-1 and thromboxane A2. Bioactive factors also affect vascular smooth muscle and enhance vascular contraction mechanisms, including cytosolic Са2+, protein kinase C, and Rho-kinase. The study empirically confirms and theoretically proves that further understanding of the interaction between bioactive factors, vascular mechanisms and molecular targets should help to develop more effective measures for early detection and prevention of preeclampsia. The results of the study will be useful for primary care physicians, gynecologists, cardiologists, therapists.